PENGARUH NPF, FDR DAN ROA TERHADAP PEMBIAYAAN BAGI HASIL PADA BANK UMUM SYARIAH - Dinda Naza Febriani; Sutan Wirman (UIN Mataram, 2021)
This study aims to test the influence of NPF, FDR, and ROA on Profit Sharing Financing. The population of this research is Sharia Commercial Banks in Indonesia and the sample used is only 3 banks that fit the criteria. The data in this study was taken from the Quarterly Financial Statements of Sharia Commercial Banks for 3 periods, from 2017-2019. The results showed that NPF and ROA had a significant effect on Profit Sharing Financing while FDR did not affect Profit Sharing Financing. The predicting ability of the three variables to The Profit Sharing Financing in this study was 14.70% while the remaining 85.30% was influenced by other factors that were not included in the research model.